Modelling and performance analysis of parabolic trough solar concentrator for different heat transfer fluids under Malaysian condition. (April 2020) - Zaharil, H.A.; Hasanuzzaman, M.
Abstract: With the increasing energy demand, depleting fossil fuel, and commitment to the Paris climate agreement, Malaysia should tap into this natural resource and harness its solar energy potential. In this research, a location in Malaysia was chosen based on its yearly direct normal irradiance (DNI) and an optimization strategy for a potential parabolic trough power plant. Besides that, an energetic and exergetic comparison and analysis between 6 HTFs (Pressurized water, Therminol VP-1, Syltherm 800, Solar salt, Hitec XL) on real-world climatic condition (based on Malaysian climatic condition) with varying inlet temperature level (300K–900K), ambient temperature and wind speed was done by using 1-D mathematical model that was coded in MATLAB®. Bayan Lepas received the highest yearly DNI and Sodium liquid outperformed other HTFs at varying DNI and inlet temperature level except at 300K with an advantage ranging between 0.036% and 0.99% in thermal efficiency and 0.438%–0.85% in exergetic efficiency to other HTFs. Sodium liquid at the temperature level of 700K also showed the strongest exergetic gained for any potential implementation of PTSC power plant in Malaysia. For climatic impact on the performance of HTFs, Energetic performance increase with ambient temperature while exergetic performance showed otherwise for all HTFs. Wind speed increment has a negligible impact on PTSC performance for all HTFs with sodium liquid's performance being the most resistant to any wind increment. Highlights: Comparison between 6 HTFs in various climatic condition was carried out. Sodium liquid performed the best at all DNI an inlet temperature level. HTFs at inlet temperature level of 700K gained the most yearly exergetic energy. Ambient temperature effects thermal and exergetic performance of all HTFs. Low DNI greatly reduces the performance of HTF at inlet temperature of ≥700K